West syndrome: ethiology, management, long-term outcomes - L. S. Krayeva; V. M. Alifirova; O. V. Grebenyuk (Бюллетень сибирской медицины)
The article is based on long-term observation of 27 patients with West syndrome, age of onset, etiology of symptomatic forms, neurological status, efficiency of hormone therapy and antiepileptic drugs.